0443 Sandstone mining: peril of silicosis. (21st August 2017) - Mittal, Ashish; Gupta, Mohit
Abstract : Approximately 25 000 workers are engaged in mining of sandstone in a small district of Madhya Pradesh, in the centre of India. Most of the quarry are small, unregistered, and unorganised, mining soft stone where silica content can be as high as 70%. 88 workers of average age of 25 years, minimum age being 13 years and maximum being 70 years were examined during a screening camp. 77 male workers and 11 female workers are engaged in the process of stone breaking, cutting, cleaning, loading and unloading for an average of 8 years of work, with minimum 1 month of work to 30 year of maximum work. These workers work under precarious conditions of high silica exposure and high risk of accidents and injuries. These workers, mostly malnourished live in very unhygienic conditions. 50% of the workers have normal pulmonary function test, and rest of the 50% workers have varying degrees of abnormal pulmonary function test, the most common being mild obstruction in 15 workers. Only one female out of 11 female workers have normal pulmonary function test. Based on detailed occupational history, clinical examination and X-ray reading as per ILO standards and their pulmonary function test outcome, 19 workers were diagnosed of Silicosis, 6 of Silico-tuberculosis. These 25 workers have a varying degrees of respiratory disability based on pulmonary function test recordings, mainly 12 having 20%, 3 having 30% disability, maximum being 100% in one of the 14 year old female worker of 1 year working history in stone quarry.